ANXIETY AND EDUCATIONAL STYLE OF MOTHERS OF HANDICAPPED CHILDREN - RUSNAC Svetlana; STRATAN Ala (EcoSoEn: Ştiinţe Economice, Sociale şi Inginereşti = Economics, Social and Engineering Sciences)
he problems of the families that educate children with disabilities have been attracting more and more attention over the last decades. Especially the relatioinships between the parents and the child and the educational style in such families are studied. Parent’s educational style is influenced by socio-cultural traditions, by the child’s clinical and psychological state, by the handicap’s ethology that influence the early contact between the child and the parents, especially mother, by the way the adults are communicating, and, most importantly, by the parent’s character. The relevance of the topic that is to be reported is created by the lack of research of the dependencies between the educational style and the parent’s anxiety, especially mother’s anxiety. The base hypothesis we verified: mother’s anxiety correlates with the chosen educational style. The research represents a comparative study with two groups of subjects: 30 mothers of children with disabilities – the experimental group, and a control group that consisted of 30 mothers with healthy children, both having completed 2 methods: 1) State-Trait Anxiety Inventory (STAI); 2) The Varga-Stolin method diagnosis of parental style. Three operational hypotheses were checked during the research. Hypothesis 1: Mothers of handicapped children have a higher anxiety level when compared to the mothers of healthy children. Even though the mothers of disabled children had a higher anxiety-state, the control group had a higher anxiety-trait, statistical comparison not showing considerable differences. The hypothesis was disproved. For both groups anxiety-state was low, anxiety-trait being moderately present in the experimental group and moderate to high in the control group. Hypothesis 2: There are different educational styles, depending on whether the child is handicapped or not. The analysis of the results showed that the control group had more pronounced attitudes of rejection, uncertainty and infantilization, and the experimental – the attitude of symbiosis, and almost equal when it came to the styles that involved cooperation and moderate control. One significant difference was spotted after the statistical analysis – that of the mean value for acceptance-rejection (p<0.02). The hypothesis was partially confirmed. Hypothesis 3. Anxiety directly corelates with educational styles that are not favorable for the child’s development and vice versa for those that are beneficial. To verify it we used the Pearson correlation test. The results showed: a) a negative relationship between anxiety-trait and educational attitudes of acceptance (p=0.05) and cooperation (p<0.05), which denotes the unfavorable role of anxiety in promoting mother-child parity relationships; a positive relationship between anxiety-trait and attitudes of control and infantilization, which illustrates the fact that fears, apprehensions, distrust ruin the child's ability to give autonomy, to treat him as an equal. Even though the reserch’s results are quite favourable, some problems with the relationship between a child with disabilities and their mother were found: the medical model being more prioritised rather than the social one, the informing of parents about the favourablee relationships and educational style being insufficient, the vulnerabilty of families and the stereotypical view upon handicaps, etc.